Evaluation of the Anthelmintic Effects of Leaf and Seed Extracts of Carica papaya in Mice Infected with Roundworm (Heligmosomoides bakeri) (Sahel Journal of Life Sciences FUDMA, 2025)
The increasing resistance of helminths to conventional anthelmintic drugs necessitates the search for safer, natural alternatives. This study evaluated the anthelmintic efficacy and safety of leaf and seed extracts of Carica papaya in mice experimentally infected with Heligmosomoides bakeri. Fresh leaves and seeds were collected, authenticated, and extracted using ethanol. Phytochemical screening revealed alkaloids (24.12 Â± 0.20 mg/100 g in leaves; 16.64 Â± 0.12 mg/100 g in seeds), saponins (5.74 Â± 0.13 and 3.89 Â± 0.07 mg/100 g), flavonoids, tannins, terpenoids, and cardiac glycosides. Acute toxicity (LDâ‚…â‚€) exceeded 5000 mg/kg, indicating a high safety margin. Infected mice were treated with 800 mg/kg of leaf extract, 800 mg/kg of seed extract, 400 mg/kg of combined extract, or 50 mg/kg of albendazole. Haematological indices remained stable (RBC: 6.49â€“7.01 Ã— 10â¶/mmÂ³; Hb: 14.00â€“15.47 g/dl), with no significant alterations in liver (AST: 41â€“43 U/L; ALT: 34â€“36 U/L) or renal parameters (urea: 18.69â€“19.66 mg/dl; creatinine: 0.76â€“0.79 mg/dl). Treatment with C. papaya extracts significantly reduced worm load compared to control, with the combined extract (400 mg/kg) achieving the greatest reduction (from 129.67 Â± 3.52 to 100.00 Â± 3.00 by day 12), while albendazole cleared the infection completely. These findings demonstrate that C. papaya leaf and seed extracts possess potent anthelmintic activity, likely due to their rich phytochemical composition, and are safe for use without adverse haematological, hepatic, or renal effects. The study supports the potential of C. papaya as a viable natural alternative for helminth control and an effective complement to synthetic anthelmintics.